Assessing the Risk of Pesticides for the Aquatic Environment: Introducing the E-flows Mesocosm, a Step Change in Higher Tier Testing. (1st February 2018) - Benstead, Rachel; Phillips, David; Black, Fraser
The methodology used to assess the risk of pesticides in the aquatic environment is based on a standardised approach referred to as the Toxicity/Exposure Ratio (TER) or Risk Quotient, and indeed this format was first developed for the aquatic compartment because a direct comparison of the Predicted Environmental Concentration (PEC) of the pesticide of concern with the Predicted No Effect Concentration (PNEC) for the relevant biota is relatively straightforward in water. Of course, there are a myriad of complications even in this assumption, but here it is proposed to look again at the most fundamental aspects of how the PNEC is derived using a tiered array of ecotoxicity tests, how relatable this is to the derivation of the PEC using mathematical models, and ultimately how well this approach represents risk to the aquatic environment. It has long been understood that the best way to assess the degree of risk from plant protection products to aquatic (non-target) organisms is to expose those organisms to relevant concentrations of the pesticide of concern in conditions that closely resemble those that occur in the relevant habitats, in this case edge-of-field waterbodies including streams, ditches and ponds in the agricultural landscape. This approach accounts for many of the natural interactions that occur between biota (competition, predation, food resources) and with the physicochemical aspects of the environment (flow, oxygenation, substrate) that can act both as additional stressors (in addition to that posed by the pesticide) and also as natural buffers to the exposure stress (through removal of that pesticide via biodegradation and binding etc). For these reasons, when the exposures made for risk assessment are close to reality, the consensus is that the need for additional measures to account for residual uncertainty is small. In contrast, and in practice, the vast majority of exposures made to assess the risk to biota are very far from realistic. Routine ecotoxicity testing is performed in closely controlled, constant laboratory conditions using organisms bred and raised for the purpose in those same conditions, some of which are clonal (to reduce further natural variation, e.g. the commonly used Daphnia species). The conditions used are considered to be optimal for the species (e.g. for temperature and day length) and the exposures are made in single species groupings or individually, in the presence of a large excess of resources. The intention is to achieve a state of little or no stress to the test organisms excepting that posed by the chemical under assessment. Because this approach is used, it becomes necessary to account for a considerable depth of uncertainty with regard to the outcome, should the same exposure be made in realistic conditions. This leads to a large factorisation of one side of the TER equation using an arbitrary, but generally accepted 'Assessment Factor' according to the type of test performed. These factors are often orders of magnitude, and of course, using this approach there is no way of understanding how close to reality the arbitrary factor actually is. For this reason, the factors must necessarily err on the side of caution, and consequently in some cases the level of precaution is likely to be extensive. Why is this approach taken for the majority of testing? There are two very good reasons. The first is a matter of practicality – while it is accepted that testing in close to real conditions is preferable to understand the uncertainty, it can also be remarkably difficult to achieve. It involves the creation of multiple, discreet but realistic simulations of natural water bodies – commonly termed Mesocosms. The second reason is essentially the other side of that coin; that laboratory testing is straightforward, relatively inexpensive and more easily reproducible, given that testing is performed according to internationally accepted Test Guidelines based on extensive ring-tests. In this context, it makes no sense to try to achieve environmentally realistic testing in the first instance, particularly where a chemical can be demonstrated to be safe for biota, even when a large assessment factor is applied. For this reason, many jurisdictions advocate a Tiered risk assessment process, beginning with controlled laboratory exposures at Tier 1. This is clearly satisfactory where there is little or no risk posed by the chemical of concern. However, there is immediately a problem where some risk is indicated, and this outcome is often apparent when exposing biota to products designed to be pesticidal. Where the TER is less than 1, there is no way to address how likely it is that the modelled risk will actually occur in the aquatic environment, given that the assessment factor is both large and arbitrary, leaving much scope for error. It may be the case that the large factorisation was justified, and the pesticide is unsafe for edge of field water bodies; or it may be the case that the size of the factor was far from justifiable, and in reality, the pesticide does not have a significant effect on aquatic populations. If it is always assumed that the pesticide is unsafe at this stage, then many potentially useful crop protection products are lost from agricultural use.